Online Sales in B2C E-Commerce Platforms: A Qualitative Study - Belbağ, Aybegüm Güngördü; Belbağ, Sedat (My University, 2024)
This study examines online shopping behavior during the pandemic in the emerging market, Turkey. The current research benefits from the Stimulus-Organism-Response framework and innovation resistance theory. We analyzed the qualitative data with thematic analysis. We carried out thirty in-depth interviews to collect qualitative data. Our findings show that environmental stimuli (crowding, product category, usefulness, past experiences, the perceived threat of COVID-19) and the organism (perceived benefits, tradition barrier, risk barrier) affect the response (shopping from online stores during the pandemic).
Keywords: İşletme; E-commerce; qualitative study; online sales; stimulus-organism-response framework; innovation resistance